(untitled) (Research, Society and Development, 2019)
The disorderly growth of urban centers, end up generating several types of disorders, mainly in the matter of pluvial drainage. Large floods end up causing several losses to society. The objective of this article was to compare and analyze the feasibility of the use of permeable concrete pavement in the street Dr. Laerte Laender, in the municipality of Teófilo Otoni / MG, in order to avoid floods caused by the lack of drainage and drainage of rainwater . In the development of the article, when interpreting the soil behavior at the indicated location, it was possible to verify a high water penetration index from 1.20 m depth in the soil, thus being feasible the implantation of a system without infiltration, channeling the water to a reservoir, whose volume determined according to the rainfall index of the region, is a value close to 7.424 m³. Therefore, despite the difficulties encountered, it is feasible to use the permeable concrete pavement in order to reduce these generated disturbances.